Annely Juda - A Celebration. - Juda, David; Lemoine, Serge; Lynton, Norbert; Nash, Steven A.; Rattemeyer, Volker; Sakai, Tadayasu; Schmidt, Katharina; Serota, Nicholas (London : Annely Juda Fine Art London, 2007)
Ackling, Roger ; Bill, Max ; Blane, Frances Aviva ; Brancusi, Constantin ; Caro, Anthony ; Charlton, Alan ; Chillida, Eduardo ; Christo ; Clough, Prunella ; Cohen, Nathan ; van Doesburg, Theo ; Foxcroft, Lesley ; Friedmann, Gloria ; Funakoshi, Katsura ; Gabo, Naum ; Girling, Sheila ; Green, Alan ; Green, June ; Hall, Nigel ; Haypeter, Werner ; Hockney, David ; Holmwood, Sigrid ; Juda, Annely ; Kadishman, Menashe ; Kalkhof, Peter ; Kawamata, Tadashi ; Kossoff, Leon ; Lago, Darren ; Leapman, Edwina ; Lee, Catherine ; Lissitzky, El ; Malevich, Kasimir ; Martin, Kenneth ; Martin, Mary ; Michaeledes, Michael ; Mondriaan, Piet ; Morellet, François ; Nash, David ; Picasso, Pablo ; Pollock, Jackson ; Popova, Liubov ; Reynolds, Alan ; Rodchenko, Alexander ; Rozanova, Olga ; Saito, Yoshishige ; Shiraga, Kazuo ; Shiraishi, Yuko ; Tatlin, Vladimir ; Treister, Suzanne ; Vantongerloo, Georges ; Vordemberge-Gildewart, Friedrich ; Williams, Graham ; Yadegar, Manijeh
Annely Juda - A Celebration, Annely Juda Fine Art London, 2007-05-24. 2007-07-28
boek